Evaluation of Soybean Meal as a Dietary Protein Source on the Performance of Labeo rohita (Ham.) Spawn Reared under Pond Condition (The Agriculturists, 2013)
Growth of Labeo rohita spawn, fed on four formulated (almost iso-nitrogenous and iso-caloric) diets containing fish meal, soybean meal, mustard oil cake and rice bran along with vitamin and mineral premix was studied at the Bangladesh Agricultural University, Mymensingh, during 07 June to 19 July, 2006. Fish meal was replaced by soybean meal at the rates of 0, 25, 50 and 75% in Treatment 1, 2, 3 and 4, respectively. In a 42-day feeding trial, significantly higher growth rate, feed conversion ratio, protein efficiency ratio and survival rate and slightly higher protein content in carcass were observed in Treatment 2 but the variation was not statistically significant. DOI: http://dx.doi.org/10.3329/agric.v11i2.17482 The Agriculturists 2013; 11(2) 14-20